The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1109/22.954788
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of the interaction between electromagnetic waves and nonlinear superconducting materials

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…By two-fluid model we can find the permittivity with respect to order parameter in all along the superconductor. The effective dielectric constant is here given by [5] ,…”
Section: Theoretical Model and Analysismentioning
confidence: 99%
“…By two-fluid model we can find the permittivity with respect to order parameter in all along the superconductor. The effective dielectric constant is here given by [5] ,…”
Section: Theoretical Model and Analysismentioning
confidence: 99%
“…In several papers, the nonlinear model was represented by a quadratic nonlinearity, whereas in other studies, different nonlinear behaviors were found to be suitable Wolff, 1996a, 1996b], especially in the presence of high magnetic fields. A quadratic nonlinearity was also assumed in a computational approach [Caorsi et al, 2001] devised for studying the interaction between an incident wave and a superconducting cylinder modeled by a negative permittivity. In the same paper, a preliminary result conceming the guided propagation has been reported with reference to the same degree of nonlinearity.…”
Section: Introduction Materials and In Particular To Devise Methodomentioning
confidence: 99%
“…and extended bySheen et al [1991] to deal with superconducting materials. In particular, a resistance matrix is constructed, whose elements are given by rib (H) --Re on_•i• -3similar to the so-called distortedwave Born approximation, which has been applied byCaorsi et al [1993] to nonlinear dielectrics and detailed byCaorsi et al [2001] for the computation of the interactions between an incident wave and a superconducting object. In particular, at each iteration, the magnetic field is obtained on the basis of the current density of the previous step, starting with the linearcase.…”
mentioning
confidence: 99%
“…Other works addressing the interaction between electromagnetic waves and nonlinear superconducting materials have been presented mainly within the microwave community. A complete study with numerical computations can be found in [8].…”
mentioning
confidence: 99%